The Analisys of The Green Economy Implementation on Sustainability Small and Medium Enterprise in lhokseumawe City - Sapna Biby; Yuli Asbar; Jufridar Jufridar (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2023)
The amount of SME’s in Lhokseumawe city was 2058 that consist of different production sector, culinary, craft and other sector under the guidance of the Industrial agency, trade, union and Small Medium Enterprises in Lhokseumawe). The sustainability of MSMEs is a problem that needs attention from researchers considering that the existence of MSMEs is very important in supporting the community's economy. Sustainability is inseparable from various factors ranging from Green Input, Green Process, Green Output, and Green Marketing. The results of the study conclude that green input has a significant effect on entrepreneur knowledge, Green Input has no significant effect on MSME sustainability, Green Marketing has no significant effect on entrepreneur knowledge, Green Marketing has no significant effect on MSME sustainability, Green process has no significant effect on entrepreneur knowledge, Green the process has a significant effect on the sustainability of MSMEs, green products have a significant effect on the knowledge of entrepreneurs, green products have a significant effect on the sustainability of MSMEs, the knowledge of entrepreneurs has a significant effect on the sustainability of MSMEs, Green Input has an insignificant effect on the sustainability of MSMEs through entrepreneur knowledge, Green Marketing has a significant effect on MSME Sustainability through entrepreneur knowledge and green products have no significant effect on MSME sustainability through entrepreneur knowledge. Lhokseumawe City Government can disseminate and provide guidance to MSME entrepreneurs regarding sustainable business that found to have a weak performances. In addition, MSME entrepreneurs could increase the awareness of the environment side to side with the business activities.